PEMANFAATAN LIMBAH KULIT DURIAN (Durio zibethinus) DAN KULIT CEMPEDAK (Artocarpus integer) SEBAGAI EDIBLE FILM - Amaliyah, Desi Mustika (Kementerian Perindustrian, 2014)
Durian (Durio zibethinus) and cempedak (Artocarpus integer) peels waste are not used by the society. The research aim is to extract pectin from durian and cempedak peels and to formulate the pectin into edible films for food packaging. The research stages were first pre-treatment of durian and cempedak peels, pectin extraction, pectin drying, andÂ pectin application as edible films with concentration of 0%, 5%, and 15%. Based on this research it was concluded that pectin can be extracted from durian and cempedak peels with yield result of 27.97 % and 55.58 %, respectively. Edible film obtained hasÂ similar characteristics between raw materials cempedak and durian peels. The higher concentration of cempedak peelÂ pectin increased the thickness, but decreased the tensile strength and elongation at a concentration of 15%. While in edible films from durian peel pectin, the higher concentration of pectin decreased the thickness of edible film on pectin concentration of 15%, lowered tensile strength and raised the edible film elongation.Keywords: waste, durian, cempedak, pectin extraction, edible film